Sistemática molecular de Utricularia L. (Lentibulariaceae) - Silva, Saura Rodrigues da [UNESP] (2014)
The use of molecular systematics in various existing approaches is currently of paramount importance to produce and supplement data concerning the identification and evolutionary history of several species. The use of the DNA molecule, combined with the current tools based on systematics, can be of great value to the proposition of a classificatory system closer to natural. The genus Utricularia L. (Lentibulariaceae) comprises about 250 species, of which about 90 occur in the Neotropics and 69 in Brazil, and 20 of these are endemic. Many species occur in a wide variety of habitats and has a high degree of structural polymorphism, by that they are commonly mistakenly identified, even by experts. Infrageneric delimitation has also inconsistencies regarding boundaries and phylogenetic relationships of the subgenera and sections, a fact that highlights the need for phylogenetic studies based mainly on molecular data. Thus there is a clear need for systematic research for the group, which could provide diagnostic information for interspecific boundaries as well as the relationships of taxa (subgenera, sections and species). Therefore, the present study was to evaluate the main objectives (i) the effectiveness of the application of DNA barcoding and (ii) hold the largest phylogenetic study already proposed for Utricularia, based on DNA sequences of nuclear and chloroplast genomes